The Application of the Principle of Due Process of Law in Arrests and Detentions Based on Electronic Evidence in Criminal Cases - Tumian Lian Daya Purba; Silvester Magnus Loogman Palit (Westscience Press, 2026)
The advancement of digital technology has significantly transformed the nature of criminal activities and the methods used in law enforcement, particularly through the increasing reliance on electronic evidence. This study aims to analyze the application of the principle of due process of law in arrests and detentions based on electronic evidence within criminal proceedings. Using a normative legal research approach, this study examines statutory regulations, legal doctrines, and relevant scholarly literature to evaluate whether current legal frameworks adequately protect individual rights. The results indicate that although electronic evidence has been formally recognized as valid legal evidence, its use as the basis for arrest and detention presents significant challenges. The absence of clear technical and procedural standards, particularly in determining “sufficient preliminary evidence,” may lead to inconsistencies and potential violations of due process. Issues related to authenticity, integrity, chain of custody, and technical validation of electronic evidence further complicate its reliability. Moreover, the complexity of digital evidence creates an imbalance between law enforcement authorities and suspects, limiting the latter’s ability to effectively challenge such evidence. This study concludes that the application of due process of law in cases involving electronic evidence remains inadequate due to gaps in the regulatory framework and limited institutional capacity. Therefore, it is necessary to strengthen legal standards, enhance judicial oversight, and develop technical guidelines to ensure that the use of electronic evidence aligns with fundamental principles of justice and human rights. This research contributes to the development of criminal law by providing a normative evaluation of the intersection between technological advancements and procedural safeguards